2001
DOI: 10.1152/ajplung.2001.281.2.l336
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil chemokine preserves alveolar development in hyperoxia-exposed newborn rats

Abstract: Inflammation may contribute to lung injury and impaired alveolar development in bronchopulmonary dysplasia. We treated hyperoxia-exposed newborn rats with antibodies to the neutrophil chemokine cytokine-induced neutrophil chemoattractant-1 (CINC-1) during 95% O2 exposure to reduce adverse effects of hyperoxia-induced inflammation on lung development. Rats were exposed at birth to air, 95% O2, or 95% O2 + anti-CINC-1 (injected on days 3 and 4). Bromodeoxyuridine (BrdU) was injected 6 h before death. Anti-CINC-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 40 publications
5
82
2
4
Order By: Relevance
“…This finding was supported by Kaplan-Meier survival analysis and log rank test, and was in contrast to studies using only a strategy of neutralization of CXCL1 for a limited period of time (50,51). Moreover, our findings demonstrate that the interactions between CXCR2 ligands and CXCR2 are paramount to the generation of an inflammatory response characterized by neutrophil sequestration and alveolar-capillary membrane injury in the adult lung.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This finding was supported by Kaplan-Meier survival analysis and log rank test, and was in contrast to studies using only a strategy of neutralization of CXCL1 for a limited period of time (50,51). Moreover, our findings demonstrate that the interactions between CXCR2 ligands and CXCR2 are paramount to the generation of an inflammatory response characterized by neutrophil sequestration and alveolar-capillary membrane injury in the adult lung.…”
Section: Discussionsupporting
confidence: 80%
“…Although previous studies have shown that using nonpeptide CXCR2 antagonist or neutralizing CXCL1 or CXCL2/3 Abs can reduced neutrophil infiltration into the lung under hyperoxic conditions (50,51,58), our study is the first to demonstrate that knockout of a single gene, CXCR2, can result in a marked survival advantage of adult mice in hyperoxia. This finding was supported by Kaplan-Meier survival analysis and log rank test, and was in contrast to studies using only a strategy of neutralization of CXCL1 for a limited period of time (50,51).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Following exposure to 80% O 2 for 6 days, CXCR2 −/− mice showed reduced neutrophil sequestration, which is associated with significantly decreased lung vascular permeability, edema and injury [121]. Furthermore, administration of neutralizing antibodies and antagonists of CXCR2 ligand, such as cytokine-induced neutrophil chemoattractant-1 (CINC-1), reduced the neutrophil mediated inflammatory responses and markedly increased survival of adult mice subjected to hyperoxia [118,122,123]. Another CXCR2 antagonist, SB265610, blocked chemokine effects on neutrophil viability and lung apoptosis in new born rats exposed to 95% O 2 for 8 days [122].…”
Section: Proinflammatory Responses In Hyperoxic Lung Injurymentioning
confidence: 99%